If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9d + -36 + -8 = 5d Reorder the terms: -36 + -8 + 9d = 5d Combine like terms: -36 + -8 = -44 -44 + 9d = 5d Solving -44 + 9d = 5d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-5d' to each side of the equation. -44 + 9d + -5d = 5d + -5d Combine like terms: 9d + -5d = 4d -44 + 4d = 5d + -5d Combine like terms: 5d + -5d = 0 -44 + 4d = 0 Add '44' to each side of the equation. -44 + 44 + 4d = 0 + 44 Combine like terms: -44 + 44 = 0 0 + 4d = 0 + 44 4d = 0 + 44 Combine like terms: 0 + 44 = 44 4d = 44 Divide each side by '4'. d = 11 Simplifying d = 11
| 2h+1-2h= | | 2(x-a)=y | | 4(3d-5)=4 | | x(7-3x)(6+x)=0 | | -3(x-8)+9=33 | | x^2-5x-204=0 | | C=0.5x | | x^2-5x+204=0 | | 40-3x=13 | | x^2+5x+204=0 | | 6(2p-1)2-54=0 | | -3=-n | | 4g+3(-6+3g)=1-g | | p-42=-42 | | -7x-2=-5x+6 | | (x^2+25)(x^2-9)=0 | | -4(-C-16)=-4-16 | | 0=t*lnt | | C=0.5x+22.4 | | 9y-5=23+2y | | 8(x+3)=38 | | 0.5x+9=-4 | | 9p-19=-61+2p | | x^2=-3x+9x | | 2(x-7)+3-5x=23 | | -3+p/6=-5 | | -6.9x+23.3831=-1.1(x-4.237) | | (-2+-2y)+3y=-4 | | 4+11x=7x-1 | | 7x+23x-5=6(5x+8) | | 10x-9=-11 | | 936-(x+24)=72 |